Prototyping Approach for User Interface Optimization of "Gowes" Bicycle Rental Mobile Application - Pratiwi, Ni Made Dara Gina; Juliuntari, Ni Kadek Vanya; Agustin, Putu Windi; Aprilia, Sindy (TECHNOVATE: Journal of Information Technology and Strategic Innovation Management, 2024)
Bali, as one of the world's leading tourist destinations, offers various tourist activities including cycling along the beach. To support these activities, an efficient and user-friendly bicycle rental system is needed. In this research, we developed and optimized the user interface (UI) of the "Gowes" bicycle rental mobile application using a prototyping method approach. The prototyping method was chosen because of its ability to create an initial model of the interface which is then tested and refined based on user feedback. The stages in this approach include requirements gathering, initial prototyping, user evaluation and testing, prototype refinement, and final implementation. By involving users in each iteration, developers can ensure that the resulting interface truly matches their needs and preferences. The results show that this approach not only increases user convenience and satisfaction but also reduces the risk of project failure. The implementation of the system using Level 0 Data Flow Diagram (DFD) provides an overview of the data flow and main processes in the application, ensuring that all features and functions run as planned. The "Gowes" application is expected to improve tourists' experience in renting bicycles and enjoying the beauty of Bali.